An evaluation of the computer aided design (CAD) curriculum of the interior design in a private university in Manila - Candelaria, Ma. Bienvenida T. (College of Home Economics, University of the Philippines Diliman, 2010)
The integration of technology in the CAD curriculum program for Interior Design students was introduced in this private university in Manila in 1998. The existing curriculum program underwent several revisions after the latest trends in software application influenced the use of CAD in the various stages of design. A management-oriented evaluation framework helped determine the effectiveness of the existing CAD Curriculum program in this private university in Manila. The study is a descriptive and evaluative approach with 62 respondents categorized into three groups comprising of students, graduates and practitioners. The sampling was purposive in nature because they were selected by referrals based on a ?prescribed criteria? (Calmorin and Calmorin 101). Open-ended questionnaires determined the latest methodology applied by practitioners in the use of AutoCAD and other related software for presentation drawings in the different stages of the design process. A close-ended survey questionnaire evaluated the performance of the three groups of respondents. Lastly, an open ended questionnaire established the recommendations in the study based on the results. Based on the responses given by 15 CAD practitioners, a minority of 8% utilize drawings in 3D format. The use of Sketch-up and 3DsMax is popular to prepare drawings in 3D format for the conceptual and design development phase. The findings of the study showed that the performance of the students were highly acceptable only in the area of presentation speed. The areas for improvement were the areas of 3D integration, integration of software application and the use of plotting devices. As a result, there was a need to further look into the current CAD program in the private university. The following recommendations were considered for the enhancement of the existing CAD curriculum program in the private university as follows: (1) the need for a curricular review on the current CAD curriculum (2) the syllabus should be revised to include other 3D software (3) the current CAD curriculum should be supplemented by six more units of CAD subjects in compliance with CMO No. 28 (4) graduates should be trained in reputable architectural and interior design firms to enhance their ability and equal the ability of CAD practitioners of at least five years (5) instructors should participate in yearly training programs for upgrade and lastly (6) facilities should be equipped with plotting devices.